Air parcel network design considering pure freighters. (September 2019) - Wang, Huaizhu; Zhang, Mengjie; Chen, Chao; Yao, Baozhen
This paper proposes a selection model of candidate nodes and an air parcel network hub location model to estimate the efficiency of the parcel network when adding pure freighters. Using the data on real demands among airports in practice, this article analyzes the hub location problem of the parcel network for DHL Express in the Asia-Pacific region. We find that Beijing, Hong Kong, Singapore, and Mascot are potential choices to be hub airports. The four hubs have parcel production of 10.1, 5.36, 2.75 and 0.84 million tons in the planning horizon, respectively. A sensitivity analysis is conducted to analyze the influence of different numbers of pure freighters on the air parcel network and the results indicate that the number of pure freighters can alleviate parcel pressure.